Temps universel ou temps international ? - Panfilo, Gianna (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
The Bureau International des poids et mesures (BIPM) is an international organization which role is to facilitate the standardization of measurements. In particular, the Time Department of the BIPM is responsible for the calculation and the publication of the Coordinated Universal Time (UTC) and of its rapid solution called UTCr. UTC is calculated with optimized algorithms using atomic clocks data compared by time links. UTC is the world time reference and can be considered an “Universal” and an “International” time scale. UTC is also used in multiple applications spread from the telecommunication, transports, Earth and space sciences need precise timing for observation, research, and modelling.